1997
DOI: 10.1590/s0102-311x1997000200013
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição da anemia em pré-escolares do semi-árido da Bahia

Abstract: The objective of this survey was to determine the prevalence of anemia and potential determinants thereof in 754 children from urban areas of seven small towns in the semi-arid region of Bahia. Hemoglobin was measured in 745 children 1 to 72 months of age. For the 6-to-72 month-old group, hemoglobin < 11.0 g/dl was considered anemia (following WHO recommendations) whereas <9.5 g/dl was considered severe anemia. The same cutoffs were used for children under 6 months, which are the same ones used in clinical-hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
21

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 7 publications
0
5
0
21
Order By: Relevance
“…One example of this diversity, in terms of the adoption of critical points of with children and adolescents from the USA The homogenous distribution by sex of iron deficiency and anemia observed in our patients, has been confirmed in other studies. 1,8,13,14 However, certain findings have pointed to increased prevalence of anemia in male children. 2,3,15 This could possibly be caused by the greater growth velocity exhibited by boys at preschool ages, resulting in increased demand for iron by the body, which is not being supplied by the diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example of this diversity, in terms of the adoption of critical points of with children and adolescents from the USA The homogenous distribution by sex of iron deficiency and anemia observed in our patients, has been confirmed in other studies. 1,8,13,14 However, certain findings have pointed to increased prevalence of anemia in male children. 2,3,15 This could possibly be caused by the greater growth velocity exhibited by boys at preschool ages, resulting in increased demand for iron by the body, which is not being supplied by the diet.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil [1][2][3] and in the state of Pernambuco, in particular, 4 studies with preschool children have found an elevated prevalence of anemia, with rates of around 40%.…”
Section: Introductionmentioning
confidence: 99%
“…10 No semi-árido baiano, a prevalência de anemia em crianças de 12 a 23 meses foi de 50%, e, entre os menores de 1 ano, de 29,9%. 1 A anemia está associada ao retardo do desenvolvimento neuropsicomotor, comprometimento da imunidade celular e diminuição da capacidade intelectual. Alguns estudos sugerem efeitos de longo prazo no desempenho cognitivo, mesmo que a deficiência de ferro seja revertida 9 .…”
Section: Introductionunclassified
“…Apenas uma das pesquisas citadasfoi baseada em estudo de base populacional abrangendo com representatividade para a totalidade do município. Estudos não representativos da população também foram os mais freqüentes em revisão bibliográfica realizada na base de dados Lilacs utilizando os mesmos critérios da OPS: apenas quatro estudos 1,7,10,15 eram baseados em amostra equiprobabilísticade um total de 36 publicações referentes à prevalência de anemia em crianças.…”
Section: Introductionunclassified
“…Em levantamento bibliográfico realizado na base de dados Lilacs, referente à anemia em crianças menores de 5 anos no Brasil, foram encontradas prevalên-cias elevadas, variando de 25 a 68% [4][5][6][7][8][9] . Esses estudos diferem muito entre si, seja em relação à faixa etária, tamanho amostral, seleção da amostra (institucional ou não) ou objetivos da pesquisa.…”
unclassified